Analysis of percutaneous kyphoplasty or short-segmental fixation combined with vertebroplasty in the treatment of Kummell disease - Wei Lu; Long Wang; Chunlin Xie; Zhaowei Teng; Gonghai Han; Rongmao Shi; Jinlong Liang; Sheng Lu (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background In recent years, short segment internal fixation combined with vertebroplasty (SSF + VP) has provided a new option for the treatment of Kummell disease (KD). The purpose of this study is to evaluate the efficacy of percutaneous kyphoplasty (PKP) and SSF + VP, to provide evidence-based medical support for the decision-making process when treating KD patients without neurological deficits. Methods Databases including MEDLINE (PubMed) and EMBASE (Ovid) (1947 to April 6, 2019) were searched for PKP and short-segmental fixation combined with vertebroplasty (SSF + VP) to treat Kummell disease in randomized controlled trials (RCTs) or cohort studies. Two investigators independently evaluated the eligibility of the studies retrieved from the databases based on the predetermined selection criteria. The postoperative evaluation indexes included operation time, bleeding volume, visual analog scale (VAS) score, Oswestry Disability Index (ODI) score, local vertebral Cobb angle, and cement leakage. When the data were significant, a random-effects model was used for analysis. In contrast, when the results showed no statistical heterogeneity, a fixed-effects model was used to estimate the overall effect sizes. Results Three retrospective case-control studies were included in the final analysis. The differences in the bleeding volume and operation time were statistically significant, and the combined weighted mean differences (WMDs) (95% CI) were − 0.204.46 (− 210.97, − 197.93) and − 98.98 (− 141.63, 56.32), respectively. The combined data showed that the differences in VAS score, ODI score, local vertebral Cobb angle, and cement leakage were not statistically significant. Conclusions This analysis demonstrates that the PKP and SSF + VP methods are safe and effective in treating Kummell disease patients without neurological symptoms. However, PKP can shorten the operation time and reduce the volume of blood loss.